2013
DOI: 10.1038/mtna.2013.9
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Effects of Triplet Repeat Oligonucleotides in Cell Models for Myotonic Dystrophy

Abstract: Myotonic dystrophy type 1 (DM1) is caused by DM protein kinase (DMPK) transcripts containing an expanded (CUG)n repeat. Antisense oligonucleotide (AON)-mediated suppression of these mutant RNAs is considered a promising therapeutic strategy for this severe disorder. Earlier, we identified a 2′-O-methyl (2′-OMe) phosphorothioate (PT)–modified (CAG)7 oligo (PS58), which selectively silences mutant DMPK transcripts through recognition of the abnormally long (CUG)n tract. We present here a comprehensive collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 48 publications
2
45
0
Order By: Relevance
“…Typically, gapmers complementary to the repeat are transfected into cells and induce RNase H cleavage 3, 61-63 . Oligonucleotides that target r(CUG) exp improve DM1-associated defects in a mouse model; however, electrostimulation was required 3, 5 and one caused muscle damage 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Typically, gapmers complementary to the repeat are transfected into cells and induce RNase H cleavage 3, 61-63 . Oligonucleotides that target r(CUG) exp improve DM1-associated defects in a mouse model; however, electrostimulation was required 3, 5 and one caused muscle damage 3 .…”
Section: Resultsmentioning
confidence: 99%
“…From DM1 cell and mouse model studies, there is significant support for considering the RNA gain-of-function toxicity the prime therapeutic target, and proof-of-concept testing has already demonstrated that antisense oligonucleotide (AON)-mediated degradation of DMPK (CUG)n transcripts or disruption of abnormal RNP complexes by RNA binding or MBNL displacement has potential therapeutic utility 29, 30, 31, 32. Hurdles that still have to be overcome for use in vivo relate to modes of administration, cell-type specificity of action, and possible immune effects of repeated treatment with AONs or small molecule drugs.…”
Section: Introductionmentioning
confidence: 99%
“…21). The antisense technology that utilizes morpholino CAG-25 oligonucleotides, 22 , 23 other chemically modified CAG repeat antisense oligonucleotides, 24 , 25 and synthetic siRNAs to target CUG repeats 26 appears to be effective in DM1 cells and mouse models of the disease. Additionally, viral vector-mediated expression of hU7-snRNA-(CAG) has shown to be beneficial in DM1 myoblasts 27 .…”
Section: Introductionmentioning
confidence: 99%